Could TachoSil application in cardiac surgery be potentially dangerous? A review of the literature - Smreczak, Maciej; Furgoł, Tomasz; Gigoń, Konrad; Ratajczak, Maksymilian; Jezierzański, Marcin M.; Miciak, Michał; Krych, Sebastian; Antończyk, Remigiusz; Hrapkowicz, Tomasz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2025)
The application of TachoSil adhesive is becoming increasingly popular in surgical procedures. A special area of surgical medicine is cardiac surgery, where the adhesive makes it possible to provide hemostasis when classic anastomotic methods are insufficient. There are numerous studies available demonstrating the perioperative efficacy of TachoSil, and its ease of use in the human population. However, studies on the inflammation caused by TachoSil are widely limited to animal experiments. There is a lack of studies on human groups on TachoSil-induced inflammation in cardiac surgery. The purpose of our paper is to review the current knowledge on the use of TachoSil in animals and the incidence of inflammation, in order to determine whether there is a need for similar human studies in cardiac surgery. The paper discusses the details of this problem based on recent scientific reports.